Loss potential and disclosures related to credit derivatives: A cross-country comparison of corporate bond funds under US and German regulation - Dominika Paula Gałkiewicz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
This study analyzes the loss potential arising from investments into CDS for a sample of large U.S. and German mutual funds. Further, it investigates whether the comments funds make on CDS use in periodic fund reports are consistent with the disclosed CDS holdings. For several funds in the U.S., the potential losses arising from selling CDS protection are almost as high as net assets, while in Germany, this potential can be even higher. Regarding the information funds provide to investors about their use of CDS, the results of the study suggest that comments on CDS contained in periodic reports are often unspecific and sometimes misleading. Thus, investors might have to analyze portfolio holdings in order to learn about the true investment behavior of funds. For instance, in Germany, funds that use more short than long CDS often state that they only use long CDS for hedging purposes. Based on the results, it seems advisable that regulators in both countries tighten rules restricting the speculative use of derivatives by funds to a reasonable level, as well as implement more standardized disclosure policies.
Keywords: G11; G15; G23; G28; 330; mutual funds; leverage; derivative; credit default swaps; disclosure